Early infection-induced natural antibody response - Klara Kubelkova (Nature Portfolio, 2021)
Abstract There remains to this day a great gap in understanding as to the role of B cells and their products—antibodies and cytokines—in mediating the protective response to Francisella tularensis, a Gram-negative coccobacillus belonging to the group of facultative intracellular bacterial pathogens. We previously have demonstrated that Francisella interacts directly with peritoneal B-1a cells. Here, we demonstrate that, as early as 12 h postinfection, germ-free mice infected with Francisella tularensis produce infection-induced antibody clones reacting with Francisella tularensis proteins having orthologs or analogs in eukaryotic cells. Production of some individual clones was limited in time and was influenced by virulence of the Francisella strain used. The phylogenetically stabilized defense mechanism can utilize these early infection-induced antibodies both to recognize components of the invading pathogens and to eliminate molecular residues of infection-damaged self cells.